The Effect of Stop Motion Video as An Examination Media on The Knowledge and Safe Behavior of PT. X Metal Casting Industry Workers in Klaten - Rachmadhani, Femmy Chandra; Herawati, Lucky; Muryani, Sri (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
A work accident is one of the risks that can occur in the metal casting industry. Workers' unsafe behavior is the primary cause of occupational accidents. The definition of unsafe behavior is any human behavior that can allow work accidents to occur to oneself or others. The preliminary study results found that 100% of workers had work accidents due to unsafe behavior, and out of 19 workers, 47.3% had insufficient knowledge about unsafe behavior. Counseling using video stop motion is one effort that can be used to overcome. This research aims to investigate the impact of counseling using video stop motion media on enhancing workers' knowledge and safety practices in the metal casting industry. This type of research is a quasi-experiment with a pre-test, post-test, and control group. The experimental group consisted of the workers in the finishing section, while the control group consisted of the workers in the induction section. The Wilcoxon test analysis reveals a significant difference in knowledge and behavior values between the pre-test and post-test, resulting from the use of video stop motion media. Media. The Mann-Whitney test showed a significant difference in the mean value of differences in knowledge and behavior in the pre-test and post-test between the experimental and control groups with a significance value of 0.000 (p <0.05). Video stop motion has the effect of increasing the value of knowledge and safe action among industry workers.